GIANT CELLS AND GIANT CELL LESIONS OF ORAL CAVITY- A REVIEW - Ashish Shrestha; Vinay Marla; Sushmita Shrestha; Manisha Neupane (Cumhuriyet Dental Journal, 2014)
Giant cells are large mononucleated or multinucleated cells that are seen in a variety of physiological as well as pathological conditions. Multinucleated giant cells (MGCs) are important mediators of tissue remodeling and repair and also for removal of foreign materials and various pathogens.  The commonly encountered giant cells arise from monocyte precursors, formed due to different mechanisms. Depending upon the mechanism of their formation these cells assume distinctly variable phenotypes.  The giant cell lesions of oral cavity have been classified on the basis of etio-pathogenesis, the presence of which at times being pathognomic. We attempt to review the basic information regarding the mechanism of formation and morphology of giant cells and its significance in the associated giant cell lesions. Also we have tried to describe the clinical, histopathological and immunohistochemical aspects of various giant cell lesions of the oral cavity.